Digital Transformation and Competitive Advantage in the Creative Industry: The Mediating Role of Organizational Agility - Irwan Yantu; Syarwani Canon; Raflin Hinelo; Irawati Abdul (Asian Journal of Management Analytics, 2026)
This study examines organizational agility as a mediator between digital transformation and competitive advantage in Gorontalo's creative industry (fashion, crafts, culinary). Using a quantitative causal-explanatory design with 120 purposively sampled respondents, data were analyzed via PLS-SEM. Results show digital transformation does not directly affect competitive advantage (β = -0.028; p = 0.877) but significantly enhances organizational agility (β = 0.834; p < 0.001). Organizational agility significantly influences competitive advantage (β = 0.680; p < 0.001) and fully mediates the relationship (β = 0.568; p = 0.001). The model explains 69.6% of agility variance and 43.2% of competitive advantage variance. We conclude digital transformation alone is insufficient; agile capabilities are essential for sustainable competitive advantage in dynamic markets.